Aplikasi Ilmu Biologi Dalam Pendidikan dan Pembangunan Berwawasan Lingkungan Berbasis Sumberdaya Alam - Ramadhanil Ramadhanil; Elijonnahdi Elijonnahdi (Biocelebes, 2011)
Biology is one of knowledge belong to basic sciences that have important roles in education and sustainable development that environmental sound. Biological science is a basic for numeral applied sciences such as Medicine, Pharmacy, Agriculture including Fishery, Animal husbandry, Forestry and soon. There is a branch of biology which have been developed rapidly namely Ecology that close related with environmental problem or sciences that study on the relationship between organism and their environment or interaction among environmental factors at a numerous ecosystem type such teresterial, fresh water, marine, forest and soon. Ecology is the study that may explain the cause of the occurrence of various phenomena and environmental issues that occur on Earth, such as floods, drought, landslides, the "algae blooming”, "silent spring", the development of infectious diseases, emergence of strange diseases like cancer caused by xenobiotics compounds, global warming, acid rain, destruction of biodiversity, etc. Key words: Biology, environmental sound development , ecology, natural resources.